Crime and Employment Destruction in Mexico: Do Firms Size and Location Matter? - Jorge O. Moreno; Eduardo Saucedo (Universidad Autónoma Metropolitana Unidad Azcapotzalco, 2020)
We study the effects of homicide and kidnapping rates on firms employment losses, identifying metropolitan and non-metropolitan localities in Mexico. We use a panel dataset for 32 sub-national states organized on a quarterly basis over the period 2011:Q1-2016:Q4, decomposed by locality population size and firm workforce size, including self-employment, micro, small, medium and large firms. Our results indicate that crime has a negative impact on employment across all localities but has a robust negative effect on employment in micro and small firms in metropolitan areas and non-metropolitan areas. An increase of one standard deviation (SD) in the homicide rate in each locality destroys 319,542 jobs countrywide, while an equivalent increase in kidnapping implies a loss of 560,705 jobs. On including in the analysis locality population size in the considered dimensions, this increase in homicide implies a reduction of 181,988 and 99,184 jobs in metropolitan and non-metropolitan areas, whereas for an equivalent increase in kidnapping the losses are 387,547 and 256,969 jobs, conditional on their respective model. Our results provide evidence of the heterogeneous damage of crime to employment, conditional on firm´s location and workforce size. JEL: J21, J23, F15, F43, K14, R10, R30.